1992
DOI: 10.1128/jb.174.3.1063-1067.1992
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of rcsB in Klebsiella K2 capsule synthesis in Escherichia coli K-12

Abstract: Escherichia coli K-12 harboring a part of the structural genes for the Klebsiella K2 capsular polysaccharide (cpsK*) expresses a large amount of K2 capsular polysaccharide as a thick capsule in the presence of plasmids carrying rmpA and rcsB. We have previously shown that expression of the Klebsiella K2 capsule in E. coli HB101 harboring cpsK* depends on the presence of rmpA, a regulatory gene from a large plasmid of Klebsiella pneumoniae Chedid (O1:K2). E. coli K-12 JM109, however, produces only a small amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Sequence analysis of a pathogenicity island carried by pLVPK has revealed a locus named rmpA2, which has been reported to enhance the colony mucoidy of various serotypes of K. pneumoniae (34). Introduction of multicopy rmpA2 could confer on E. coli HB101 the ability to produce Klebsiella K2 capsule in the presence of K2 cps gene cluster, and the transcription of a long-strand mRNA from K2 cps operon was simultaneously increased (1,33). These findings indicated that RmpA2 functions as a trans-acting activator for the CPS biosynthesis.…”
mentioning
confidence: 58%
“…Sequence analysis of a pathogenicity island carried by pLVPK has revealed a locus named rmpA2, which has been reported to enhance the colony mucoidy of various serotypes of K. pneumoniae (34). Introduction of multicopy rmpA2 could confer on E. coli HB101 the ability to produce Klebsiella K2 capsule in the presence of K2 cps gene cluster, and the transcription of a long-strand mRNA from K2 cps operon was simultaneously increased (1,33). These findings indicated that RmpA2 functions as a trans-acting activator for the CPS biosynthesis.…”
mentioning
confidence: 58%
“…Recently, we succeeded with the cloning and expression of the Klebsiella cps cluster in E. coli HB101 (1). Moreover, we subsequently found that the Klebsiella cps cluster requires the functions of both rmpA2 (41) and rcsB (3,37) for production of Klebsiella K2 CPS in E. coli K-12 (40). In the present report, we show the genomic organization of a region which contains the cps genes of K. pneumoniae Chedid.…”
mentioning
confidence: 79%
“…The involvement of RcsB in Klebsiella K2 capsule biosynthesis of the recombinant E. coli K-12 has been demonstrated (44). Previous studies have found that RcsB must interact with RcsA to form a heterodimer in order to bind specifically to the cps promoter for transcription initiation (21).…”
Section: Discussionmentioning
confidence: 99%